Implementation of Problem Based Learning and Project Based Learning Approaches in Fiqh Subjects at MTs Al Munawwaroh - Ridwan, Wawan; Wastiah (Jurnal Profesi Guru Indonesia, 2024)
This study aims to describe the application of Problem Based Learning (PBL) and Project Based Learning (PjBL) approaches in Fiqh learning at MTs. Al Munawarroh Sukaresik Tasikmalaya, and to analyze its impact on students' activeness and understanding. In the context of Fiqh learning which tends to be theoretical, the application of problem-based and project-based approaches is a strategic innovation to increase student involvement actively and contextually. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the application of PBL helps students develop critical thinking skills in solving everyday Islamic law problems, while PjBL encourages them to produce real work that is relevant to Fiqh material. The combination of these two approaches is able to increase learning motivation, deepen conceptual understanding, and foster an attitude of responsibility and cooperation in groups. Thus, the application of PBL and PjBL is considered effective in improving the quality of Fiqh learning at MTs. Al Munawarroh Sukaresik Tasikmalaya.